Evolution : making sense of life - Zimmer, Carl, 1966-; Emlen, Douglas John, 1967- (Greenwood Village, CO : Roberts and Company Publishers, 2013)
"Science writer Carl Zimmer and evolutionary biologist Douglas Emlen have teamed up to write a textbook intended for biology majors that will inspire students while delivering a solid foundation in evolutionary biology. Zimmer brings the same story-telling skills he displayed in The Tangled Bank, his 2009 non-majors textbook that the Quarterly Review of Biology called "spectacularly successful." Emlen, an award-winning evolutionary biologist at the University of Montana, has infused Evolution: Making Sense of Life with the technical rigor and conceptual depth that today's biology majors require. Students will learn the fundamental concepts of evolutionary theory, such as natural selection, genetic drift, phylogeny, and coevolution. Evolution: Making Sense of Life also drives home the relevance of evolution for disciplines ranging from conservation biology to medicine. With riveting stories about evolutionary biologists at work everywhere from the Arctic to tropical rain forests to hospital wards, the book is a reading adventure designed to grab the imagination of the students, showing them exactly why it is that evolution makes such brilliant sense of life"--
"Students will learn the fundamental concepts of evolutionary theory, such as natural selection, genetic drift, phylogeny, and coevolution. Evolution: Making Sense of Life also drives home the relevance of evolution for disciplines ranging from conservation biology to medicine"--
Machine generated contents note: Chapter 1: The Virus and The Whale: How Scientists Study Evolution -- Chapter 2: The Evolution of Evolution: From Natural Philosophy to Darwin -- Chapter 3: What The Rocks Say: How Geology and Paleontology Reveal the History of Life -- Chapter 4: The Tree of Life: How Biologists Use Phylogeny to Reconstruct the Deep Past -- Chapter 5: Raw Material: Heritable Variation Among Individuals -- Chapter 6: The Ways of Change: Drift and Selection -- Chapter 7: Natural Selection All Around: Empirical Examples of Natural Selection -- Chapter 8: The History in Our Genes: Using Molecular Phylogeny To Understand Evolution -- Chapter 9: Adaptations: From Genes to Traits -- Chapter 10: Sex: Causes and Consquences -- Chapter 11: After Conception: The Evolution of Parental Care and Life Histories -- Chapter 12: On the Origin of Species: Mechanisms of Speciation -- Chapter 13: Macroevolution: Radiations, Extinctions, and the Grand Patterns of History -- Chapter 14: Coevolution: The Intimate Partnerships of Nature -- Chapter 15: Minds and Microbes: The Evolution of Behavior -- Chapter 16: A New Kind of Ape: Human Evolution -- Chapter 17: Evolutionary Medicine: Using Darwin's Principles to Understand Human Health.
Includes bibliographical references and index.
Keywords: Evolution (Biology); SCIENCE / Life Sciences / Evolution